Effect of fabric orientations on mechanical properties of hybrid jute-ramie reinforced unsaturated polyester composites - M. H. M., Hamdan; Siregar, J. P.; Tezara, C.; Rusiyanto, R.; Oumer, A. N.; J., Jaafar; M., Zalinawati (IOP Publishing Ltd., 2021)
Jute and ramie fibre received significant attention from the researcher around the globe due to the excellent performance as reinforcement materials for the composite. The present work study the influence of the fabric orientation and layering sequence on the hybrid woven jute-ramie reinforced unsaturated polyester resin (UPE) on mechanical properties (tensile, flexural and impact). The composite sample was prepared via a hand lay-up method with a compression machine. Four (4) different orientation ready for the composite sample consists of 0 laminate, [0°/0°/0°/0°], cross-ply [0°/90°/90°/0]° laminate, angle-ply laminate [45°/-45°/45°/-45°] and quasi-isotropic laminate [0°/45°/-45°/90°]. Based on the finding on the current research, the effect of orientation for hybrid woven jute-ramie is apparent on the tensile testing — nonetheless, the influence of the woven orientation for flexural testing and charpy impact testing. Based on the tensile testing, the composite with the woven orientation of cross-ply yield the highest average tensile strength compared to the other composite. In the case of tensile modulus, the composite sample becoming more ductile when arranged to the orientation of angle-ply laminate and quasi-isotropic laminate. For the flexural testing and charpy impact testing, the entire composite yield almost similar value regardless of the type of woven arrangement.